2011
DOI: 10.1111/j.1468-3083.2011.04310.x
|View full text |Cite
|
Sign up to set email alerts
|

Papulopustular rosacea, skin immunity and Demodex: pityriasis folliculorum as a missing link

Abstract: Papulopustular rosacea (PPR) is a common facial skin disease, characterized by erythema, telangiectasia, papules and pustules. Its physiopathology is still being discussed, but recently several molecular features of its inflammatory process have been identified: an overproduction of Toll-Like receptors 2, of a serine protease, and of abnormal forms of cathelicidin. The two factors which stimulate the Toll-like receptors to induce cathelicidin expression are skin infection and cutaneous barrier disruption: thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
203
1
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(228 citation statements)
references
References 62 publications
10
203
1
14
Order By: Relevance
“…Skin inflammation also correlates with mite density on the skin of rosacea-affected patients [62]. Thus, the mite may participate in the exacerbation of disease either by disrupting the skin barrier [14, 63], or by triggering TLR2 activation through chitin in the insect’s cuticle [64, 65]. Furthermore, it has been reported that bacteria that live in the digestive tract of Demodex are released into the surrounding skin tissues, thereby triggering further tissue degradation and inflammation [66, 67].…”
Section: The Skin Microbiome In Human Diseasementioning
confidence: 99%
“…Skin inflammation also correlates with mite density on the skin of rosacea-affected patients [62]. Thus, the mite may participate in the exacerbation of disease either by disrupting the skin barrier [14, 63], or by triggering TLR2 activation through chitin in the insect’s cuticle [64, 65]. Furthermore, it has been reported that bacteria that live in the digestive tract of Demodex are released into the surrounding skin tissues, thereby triggering further tissue degradation and inflammation [66, 67].…”
Section: The Skin Microbiome In Human Diseasementioning
confidence: 99%
“…The literature offers numerous arguments supportive of the theory that rosacea is primarily connected with compromised immunity (Forton, 2012). According to this theory, on the skin of healthy, immune-competent individuals, the proliferation of Demodex mites is kept under control.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological agents that target inflammatory pathways associated with rosacea have historically been the focus of therapy [1,5], with topical metronidazole or azelaic acid and oral antibacterials (mainly of the tetracycline class) being widely used for this reason [5]. In addition, there is growing interest in using agents that have supplementary anti-parasitic properties, as there is potential for commensal Demodex mite overgrowth to be involved in rosacea pathophysiology [1,6]. The Demodex load of rosacea skin is increased (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The Demodex load of rosacea skin is increased (i.e. more than five mites/cm 2 ) in some individuals with rosacea [7][8][9], which may possibly exacerbate inflammation [6,10].…”
Section: Introductionmentioning
confidence: 99%